“What I Believe” di Edward Morgan Forster tra ironia e disincanto (TEST Ticontre. Theory Text Translation, 2024)
The first Italian translation of the essay What I Believe by Edward Morgan Forster is offered here. Under the shadow of Second World War, the author illustrates his ideal of humanity and civilization, by defending liberal values against the threat of totalitarianisms. The target text is preceded by an introduction, which analyses the essay within the context of Forster’s commitment as a public intellectual and discusses the translation strategies adopted. Il contributo propone la prima traduzione italiana del saggio What I Believe (1939) di Edward Morgan Forster. L’autore, dinanzi alla minaccia della seconda guerra mondiale, sintetizza il proprio ideale di civiltà e umanità, proponendo la difesa dei valori liberali dalle insidie del totalitarismo. La traduzione è accompagnata da una nota introduttiva, in cui si analizza il saggio nel quadro dell’impegno pubblico di Forster come intellettuale e si discutono le strategie traduttive impiegate.